Perlindungan Hukum Terhadap Koperasi Simpan Pinjam Terkait Kredit Macet - Purba, Bonaraja; Hasyim, Hasyim; Siregar, Dicky Syamhenri; Nadeak, Royan Abel; Surbakti, Billy Sugianta (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
This scientific work discusses the legal protection of savings and loan cooperative funds related to bad credit in the city of Denpasar because bad credit can have an impact on the funds owned and the health of savings and loan cooperatives, especially in the city of Denpasar. This scientific work uses empirical research methods, namely an approach by looking at a legal reality in society from legal theories by conducting research directly into the field to get accurate truths. The conclusion from this scientific work is that savings and loan cooperatives in the city of Denpasar in practice provide credit by entering into an agreement accompanied by collateral. The protection of savings and loan cooperative funds is the responsibility of the cooperative and its management as executors of the activities carried out by the cooperative.